Fission yeast CSL proteins function as transcription factors - Oravcová, Martina; Teska, Mikoláš; Půta, František; Folk, Petr; Převorovský, Martin (PloS one, 2013)
BACKGROUND: Transcription factors of the CSL (CBF1/RBP-Jk/Suppressor of Hairless/LAG-1) family are key regulators of metazoan development and function as the effector components of the Notch receptor signalling pathway implicated in various cell fate decisions. CSL proteins recognize specifically the GTG[G/A]AA sequence motif and several mutants compromised in their ability to bind DNA have been reported. In our previous studies we have identified a number of novel putative CSL family members in fungi, organisms lacking the Notch pathway. It is not clear whether these represent genuine CSL family members. METHODOLOGY/PRINCIPAL FINDINGS: Using a combination of in vitro and in vivo approaches we characterized the DNA binding properties of Cbf11 and Cbf12, the antagonistic CSL paralogs from the fission yeast, important for the proper coordination of cell cycle events and the regulation of cell adhesion. We have shown that a mutation of a conserved arginine residue abolishes DNA binding in both CSL paralogs, similar to the situation in mouse. We have also demonstrated the ability of Cbf11 and Cbf12 to activate gene expression in an autologous fission yeast reporter system. CONCLUSIONS/SIGNIFICANCE: Our results indicate that the fission yeast CSL proteins are indeed genuine family members capable of functioning as transcription factors, and provide support for the ancient evolutionary origin of this important protein family.
Keywords: Base Sequence; buněčný cyklus; Cell Cycle; Schizosaccharomyces; konzervovaná sekvence; Active Transport, Cell Nucleus; responzivní elementy; sekvenční homologie aminokyselin; Sequence Homology, Amino Acid; reportérové geny; transkripční faktory; Genes, Reporter; Response Elements; Schizosaccharomyces pombe Proteins; sekvence nukleotidů; Transcription Factors; aktivní transport - buněčné jádro; Animals; zvířata; mutace; Schizosaccharomyces pombe - proteiny; DNA, Fungal; Conserved Sequence; Mutation; DNA fungální